Research Partnerships in Early Childhood Education Teachers and Researchers in Collaboration - Duncan, Judith; Conner, Lindsey; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Duncan and Conner demonstrate how collaborative research on early childhood education results in gains for educators, researchers, and children alike. Drawing on examples of successful partnerships from Canada, Australia, and New Zealand, they set out the successes, struggles, insights, and opportunities that come from such partnerships.
Keywords: Science; Science; Science, general